Circulating vitamin D concentration and risk of prostate cancer: a dose–response meta-analysis of prospective studies - Gao JL; Wei W; Wang G; Zhou HL; Fu YW; Liu N (Dove Medical Press, 2018)
Jialin Gao, Wei Wei, Gang Wang, Honglan Zhou, Yaowen Fu, Nian Liu Department of Urology, The First Hospital of Jilin University, Changchun, People’s Republic of China Background: Though many studies have been performed to elucidate the association between circulating vitamin D and prostate cancer, no conclusive result is available. We carried out a dose–response meta-analysis to quantitatively examine the association of circulating 25-hydroxyvitamin D (25[OH]D) concentration with prostate cancer.Methods: Only prospective studies examining the associations of circulating 25[OH]D concentration with prostate cancer were eligible for the meta-analysis. A random-effect meta-analysis was done first, to calculate the summary relative risk (RR) and 95% confidence intervals (CIs) comparing the higher concentration with the lower concentration of 25[OH]D. A dose–response meta-analysis using random-effects model was then carried out to evaluate the nonlinearity and calculate the summary RR caused per 10 ng/mL increment.Results: Nineteen prospective cohort or nested case–control studies were included. Higher 25[OH]D concentration was significantly correlated with elevated risk of prostate cancer (RR =1.15, 95% CI 1.06–1.24). No nonlinear relationship was found between 25[OH]D concentration and risk of prostate cancer (P=0.654). Dose–response meta-analysis showed that the summary RR caused per 10 ng/mL increment in circulating 25[OH]D concentration was 1.04 (95% CI 1.02–1.06). Subgroup analysis also found a modest dose–response relationship. Funnel plot and Egger’s test did not detect publication bias.Conclusion: The findings suggest that highest 25[OH]D concentration is correlated with elevated risk of prostate cancer and a modest dose–response effect exists in this association; however, more studies are needed. Keywords: vitamin D, prostate cancer, dose–response meta-analysis